Measuring chronic multidimensional poverty - Alkire, S; Apablaza, M; Chakravarty, S; Yalonetzky, G (Elsevier, 2017)
This paper adopts a new approach to the measurement of chronic multidimensional poverty. It relies on the counting approach of Alkire and Foster (2011) for the measurement of multidimensional poverty in each time period, and then on the duration approach of Foster (2009) for the measurement of multidimensional poverty persistence across time. The proposed indices are sensitive both to (i) the share of dimensions in which people are deprived and (ii) the duration of their multidimensional poverty experience. A related set of indices is proposed to measure transient poverty. An empirical illustration is provided for Chile between 1996 and 2006.